Buddy and Earl Go to School - Fergus, Maureen; Sookocheff, Carey 1972- (Toronto : Groundwood Books/House of Anansi Press, 2017)
"Buddy and Earl know that with the right education they can become anything--even a dentist or a hot-dog vendor. So they eagerly gather their silly, smelly supplies and head to school. Soon after they arrive, their teacher, Miss Meredith, is called away and Professor Earl takes charge of the classroom"--
Keywords: Dogs -- Juvenile fiction; Hedgehogs -- Juvenile fiction; Schools -- Juvenile fiction; Friendship in children -- Juvenile fiction; Dogs -- Fiction; Hedgehogs -- Fiction; Schools -- Fiction; Friendship -- Fiction